Using a Gyro as a Tool for Continuously Variable Lateral Stabilisation of Dynamic Bipeds - N. M. Mayer; K. Masui; M. Browne; M. Asada; M. Ogino (Applied Bionics and Biomechanics)
We present simulations of different types of biped walking machines that are stabilized in the lateral direction by adding a gyro. The simulations show that, in principle, it is indeed possible to stabilise biped walking machines. Examples presented in this work include a three-dimensional version of the simplest walking model, which is based on earlier investigations, and an actuated biped robot. Here, the gyro is used as a reaction wheel. Finally, a rotor–brake combination is outlined that was used in an artistic biped robot at the Aichi World Exhibition.